THEORETICAL CONSIDERATIONS REGARDING THE USE OF SEMICONDUCTOR DIODES - Rodica Maria NEGREA (Fiabilitate şi Durabilitate)
The paper presents theoretical aspects regarding the simplest electronic component, the diode and the way in which the function of transforming the alternating current into direct current, allows the use of this electronic device in the field of IT, energy, electronics and so on. The principle of operation, the characteristics of the diode polarized directly and vice versa, the diode equation and their classification are presented.